ON THE PROBLEM OF NONADDITIVITY IN TWO - WAY ANALYSIS OF VARANCE OF DATA FOR COMPARING THE EFFICIENCY OF FISHING GEARS - NAIR, A. K KESAVAN; ALAGARAJA, K (Fishery Technology, 2017)
To bring out the relative efficiency of various types of fishing gears, in the analysis of catch data, a combination of Tukey's test, consequent transformqtion and graphical analysis for outlier elimination has been introduced, which can be advantageously used for applying ANOV A techniques, Application of these procedures to actual sets of data showed that nonadditivity in the data was caused by either the presence of outliers, or the absence of a suitable transformation or both. As a corollary, the concurrent model: Xii = Î¼ + Î±i + Î²Ê² +Î»Î±iÎ² Ê² + EiÊ² adequately fits the data.